Influence of nanocrystal distribution on electroluminescence from Si+-implanted SiO2 thin films - Ding, Liang (2011)
Light emitting diodes (LEDs) based on a metal-oxide-semiconductor-like (MOS-like) structure with Si nanocrystals (nc-Si) embedded in SiO2 have been fabricated with low-energy ion implantation. Under a negative gate voltage as low as ~-5 V, both visible and infrared (IR) electroluminescence (EL) have been observed at room temperature. The EL spectra are found to consist of four Gaussian-shaped luminescence bands with their peak wavelengths at ~460, ~600, ~740, and ~1260 nm, in which the ~600-nm band dominants the spectra. The EL properties have been investigated together with the current transport properties of the Si+-implanted SiO2 films. A systematic study has been carried out on the effect of the Si ion implantation dose and the energy on both the current transport and EL properties. The mechanisms of the origin of the four different EL bands have been proposed and discussed.